Proceedings of the 22nd ACM Conference on Hypertext and Hypermedia 2011
DOI: 10.1145/1995966.1995997
|View full text |Cite
|
Sign up to set email alerts
|

Social capital increases efficiency of collaboration among Wikipedia editors

Abstract: In this study we measure the impact of pre-existing social capital on the efficiency of collaboration among Wikipedia editors. To construct a social network among Wikipedians we look to mutual interaction on the user talk pages of Wikipedia editors. As our data set, we analyze the communication networks associated with 3085 featured articles -the articles of highest quality in the English Wikipedia, comparing it to the networks of 80154 articles of lower quality. As the metric to assess the quality of collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…The result was confirmed in German Wikipedia [17]. The social capital of the editors could also affect the quality of the articles they contributed [18]. Recently, Suzuki applied the idea of using h-index on academic ranking for assessing the quality of an article [19].…”
Section: A Using Editor-based Informationmentioning
confidence: 79%
“…The result was confirmed in German Wikipedia [17]. The social capital of the editors could also affect the quality of the articles they contributed [18]. Recently, Suzuki applied the idea of using h-index on academic ranking for assessing the quality of an article [19].…”
Section: A Using Editor-based Informationmentioning
confidence: 79%
“…The assumption behind Linus' Law is that with the number of contributors, the quality of the product increases, an assumption which has been proven for Wikipedia, where the quality of an article increases with the number of contributors who work on it [107][108][109]. While Haklay et al [110] found that the law generally applies to OSM positional accuracy, Mooney and Corcoran [111,112] could not identify a similar pattern when analyzing heavily edited objects in OSM.…”
Section: Data Trust and Vandalismmentioning
confidence: 99%
“…Zhu et al (2011) found strong evidence of shared leadership in Wikipedia, with editors in peripheral roles producing a large proportion of leadership behaviors. Nemoto et al (2011) examined the influence of pre-existing social capital on the efficiency of collaboration among Wikipedia editors, and found that higher social capital helps improve the efficiency of editors. While these studies shed light on important aspects that affect the success of peer production systems, a major limitation of these studies is that they fail to consider the broader social environment in which project participants coordinate and collaborate.…”
Section: Introductionmentioning
confidence: 99%